Entangled Bonds: Unraveling Familial Dynamics of Institutional Older Adults (London Journal of Research In Humanities and Social Sciences, 2025)
This paper explores the complex dynamics of familial relationships experienced by institutionalized older adults, focusing on the interplay between solidarity-conflict and ambivalence. Through qualitative interviews with twenty respondents residing in an old age home in Lucknow, Uttar Pradesh, the study delves into the emotional and social ties that older adults maintain with their families post-institutionalization. The findings reveal that these relationships are marked by ambivalence, where feelings of care and attachment coexist with conflict and estrangement. Many respondents expressed a sense of solidarity with their families, emphasizing the emotional and financial support they received prior to moving into the institution. However, this solidarity was often coupled with feelings of abandonment, disappointment, or conflict, primarily due to unmet expectations of caregiving or perceived neglect from their children and relatives. The study highlights how institutionalization reshapes familial bonds, leading to emotional ambivalence. For some, the institutional setting provides an escape from family conflicts, while for others, it exacerbates feelings of isolation. By analyzing narratives from the respondents, this paper contributes to the broader discourse on older adult, family relations, and institutional care, offering insights into the emotional complexities faced by older adults in institutional settings.
Keywords: Kenya.; professional regulation; public management; regulatory quality; socio-economic transformation; whole-of-government approach; Migration.; Culture; Gun Island; Environmental Crisis; Sundarbans; Legends.; Liberation Ecclesiology; Theology of History; Church History; quality; terminology; authenticity; Restoration; archaeological ceramics; museum object; functions; type; signs; properties; social capital; Institutionalization; older adults; Solidarity-Conflict and Ambivalence